Intravascular fasciitis in foot - a rare entity in a rare site - Ashitha Nanaiah; Padmapriya Jaiprakash; Annappa Kudva; Kanthilatha Pai (Our Dermatology Online, 2016)
Intravascular fasciitis is a rare lesion involving blood vessels, showing proliferation of myofibroblasts, involving the superficial or deep fascia. We report a case of middle aged male patient presenting with callosity over the toe, with features of intravascular fasciitis, which is a rare site.